THE COMPREHENSIVE STUDY ON POLLUTION INDUCED ASTHMA IN YOUNG CHILDREN - Dr. Rohit; Dr. Garima karwasra; Dr. Ravi; Dr. Shekhar Saini (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Air pollution has been linked to respiratory diseases, including asthma. Particulate matter (PM), especially PM2.5, is a major concern due to its ability to penetrate deep into the lungs and trigger inflammation.Objective: This study aimed to investigate the relationship between short-term exposure to pollution and the onset and exacerbation of childhood asthma.